An enhanced rotary compressor with gas injection through a novel end-plate injection structure. (25th February 2018) - Wang, Baolong; Liu, Xingru; Shi, Wenxing; Ding, Yunchen
Highlights: A novel end-plate injection structure to enhance the rolling piston compressor is proposed. Injection port area of the proposed system is 13 times larger than the traditional one. Mass injected into the compressor is increased 2.3 times by new injection structure. New injection structure increases heating capacity 12.5–18.2% over the traditional injection system. New injection structure increases COP 0.8–3.5% over the traditional injection system. Abstract: The gas-injected single-cylinder rotary compressor has potential in better seasonal performance than the twin-cylinder rotary compressor for air conditioning application. However, the gas-injected single-cylinder rotary compressor with traditional injection structure could not improve the thermodynamic performance as expected. Analysis shows that back-flowing of injected gas into the suction tube, quite limited injection port area, too early or too late closure of the injection port under variable working conditions are the main reasons. In this paper, a novel end-plate injection structure to overcome the shortcomings of the traditional vapor injection structures and maximize the mass of the injected gas under arbitrary working conditions are proposed. Based on geometrical analysis, the space on the end-plate for drilling the injection port without back-flowing is investigated. The results indicated that the injection region for the proposed end-plate injection structure are always existed and the injection port can be substantially enlarged. Furthermore, the performance of the rotary compressor with the traditional end-plate injection and with the proposed gas injection configuration are comparatively studied.